Financial Performance and ESG in the EU’s Core: Effects of the Russian-Ukraine War and Post-COVID Recovery - Hansen, Jackie Damkjær; Xie, Zhuyun (International Journal of Economics and Financial Issues, 2025)
This study examines the impact of sustainability efforts on financial performance by analyzing the relationship between Environmental, Social, and Governance (ESG) scores and financial performance in 653 companies across the European Union, with a focus on the "Blue Banana" region during the economic instability caused by the COVID-19 pandemic and the Russia-Ukraine war. Using financial indicators such as ROA, ROE, and ROI, the research challenges the belief that sustainability drives financial success and mitigates risks during periods of economic instability. The findings reveal a significant negative effect of the ESG disclosure score on ROA and ROI, while ROE remains unaffected. Companies with higher ESG scores incur additional costs related to sustainability, which can hinder short-term profitability and asset efficiency. Larger and older companies perform better financially, highlighting the role of operational maturity. Additionally, the environmental score negatively impacts ROA due to the costs associated with sustainability practices. These results suggest that the economic trade-offs of ESG integration are more pronounced during periods of instability, offering valuable insights for policymakers and business leaders. This paper contributes to the debate on corporate sustainability in mature markets during economic turmoil, questioning the presumed link between sustainability and financial performance in times of crisis.